Monitoramento hidrossedimentométrico e avaliação de métodos de cálculo da descarga sólida total no Rio Vacacaí Mirim - Schmidt Filho, Osmar (2016)
The monitoring of flood events provide the study of the flow generated during the rains, as well as the production and sediment transport in rural and urban watersheds providing monitoring data for future applications. The work was carried out in a section of Vacacaí Mirim river near the municipality of Restinga Sêca / RS of October 02, 2014 in December 3, 2015 with 16 events monitored with liquid discharge measurement (Q) and solid discharge after occurrence of rainy events. The objective is to perform the temporal assessment of sediment yield and some methods of calculations to estimate sediment transport to the section in the study were quantified solid discharges of the cross section and the characterization of particle sizes of the transported materials. Were determined the solid and liquid discharges for the 2014 period and 2015 in order to evaluate them temporally with the solid and liquid discharges between 2007-2015 using the Pearson correlation coefficient (r) and coefficient of determination (r²).To analyze the results and point out that indirect method of calculation to estimate sediment transport is the most suitable for the current study and compare them with previous studies using the dispersion index (DI) proposed by Aguirre et al. (2004).. The suspended material was shown to be almost all of the solid discharge in river. The granulometric composition of this material is the predominance of silt (58.3%) Sand then (28.4%) and clay (13.4%). For the material bed and drag, there was a predominance of sand, followed by silt and clay. The total solid monthly discharge to the measurement section to 2014-2015 was 117554.62 tons in 15 months evaluated. For the period 2007-2015 the total discharge was 141,039.37 tons/year. The most appropriate methods for the total solid discharge were Einstein's methods modified by Colby and Hembree (1955), Colby (1957), which include the measured sediment concentration data, dispersion index (DI) 0.09 and 2.30 respectively. Predictive methods for overall solid discharge the most appropriate methods were Toffaleti (1969) with value DI = 1.42, Engelund & Hansen (1967) DI = 2.38, Ackers and White (1973) DI = 2.44, Laursen (1958) DI = 4.07 and Yang (1973) DI = 9.42 and unloading solid bed best results were obtained by the methods of Van Rijn (1984) DI = 0.77, Karim (1998), DI = 1.66, Meyer-Peter and Müller (1948) with 6.08 DI.